Removal of zinc, lead and nickel from contaminated soil by electro-kinetic technology under the influence of washing and buoyance forces with different purging solutions. Issue 8 (24th May 2022) - Faisal, Ayad A. H.; Alkhateeb, Rasha W.; Al-Hashimi, Osamah A.; Shubbar, Ali; Saleh, B.
ABSTRACT: The effects of the washing process, purging solution, and buoyance force (inclined topography action) on the effectivity of the electro-kinetic method used to remediate of a silty clay loam and natural soils contaminated with Zn, Pb and/or Ni were investigated by applying 12 different experiments. The results revealed that the washing process and buoyance force can cause a small increase in the Zn removal efficiency (≤ 31%) when compared with non-washing approach using distilled water purging solution. Using 0.1 M of EDTA solution for the soil contaminated with listed metals in combination with washing can lead to significant increase in the removal efficiencies with percentages not greater than 58.4, 60.68 or 42.8%, respectively. In the presence of EDTA, however, the majority of metals passed through the soil media to the anode area. In contrast, these metals are accumulated near the cathodic region in the presence of distilled water. The results demonstrated that the buoyance force (resulted from inclination angle of 30°) with EDTA had adverse influence on the metal profile along the treated soil. Finally, the results certified that EDTA in electro-kinetic process coupled with soil washing is a new hybrid technique which achieved Pb removal efficiency from natural soil reached to 58% by improving the solubilization and transport of metal ions.